2011
DOI: 10.1152/ajpendo.00065.2011
|View full text |Cite
|
Sign up to set email alerts
|

Role of diabetes- and obesity-related protein in the regulation of osteoblast differentiation

Abstract: Although thyroid hormone (TH) is known to exert important effects on the skeleton, the nuclear factors constituting the TH receptor coactivator complex and the molecular pathways by which TH mediates its effects on target gene expression in osteoblasts remain poorly understood. A recent study demonstrated that the actions of TH on myoblast differentiation are dependent on diabetes- and obesity-related protein (DOR). However, the role of DOR in osteoblast differentiation is unknown. We found DOR expression incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The cells were then treated with βGP ± AA for 72 hrs, before being rinsed with PBS and permeabilized with ALP activity buffer containing 0.1% triton X-100 in 250 mM NaHCO3. Protein concentration was determined by the BCA method (Thermo Fisher Scientific; Waltham, MA) and ALP activity was detected as previously described [27] .…”
Section: Methodsmentioning
confidence: 99%
“…The cells were then treated with βGP ± AA for 72 hrs, before being rinsed with PBS and permeabilized with ALP activity buffer containing 0.1% triton X-100 in 250 mM NaHCO3. Protein concentration was determined by the BCA method (Thermo Fisher Scientific; Waltham, MA) and ALP activity was detected as previously described [27] .…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear extracts of RAW264.7 cells expressing MLV-Cldn-18, MLV-Cldn-18 ΔPDZ, and MLV-β-Gal were prepared as reported elsewhere (35). Protein concentration was determined by Bradford method and immunoblotting was carried out as described (36). Membranes were probed with antibodies against Cldn-18 (C-term) (1:250) (Invitrogen, Carlsbad, CA), ZO-2 (R-19) (1:250) (Santa Cruz Biotechnology Inc, Santa Cruz, CA), Histone H3 (1:10,000) (Sigma Aldrich, St. Louis, MO), and β-actin (1:10,000) (Sigma Aldrich, St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have shown that diabetes-and obesityrelated protein (DOR), a key modulator of TH function in muscle cells, is differentially regulated by TH and acts as a stimulatory mediator of TH effects in osteoblasts (91).…”
Section: Effects Of T3 In Bone Cells In Vitro Chondrocytesmentioning
confidence: 99%